2019
DOI: 10.1177/1465116519835947
|View full text |Cite
|
Sign up to set email alerts
|

European Monetary Union reform preferences of French and German parliamentarians

Abstract: This study analyzes results from an original survey of members of the French and German parliaments (Assemblée Nationale, Sénat and Bundestag) on economic policies and institutions of the Eurozone. We find that French politicians are significantly more supportive of Eurobonds, a European unemployment insurance scheme, and an active monetary policy by the ECB than German politicians. At the same time, there are significant differences along party lines, which are often quantitatively more important than differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In line with H1, for the SSM and SRM/SRF, where German public opinion and economic interests were sceptical towards the EU's plans, but public salience was lower, the government parties took on board the interests of stakeholders and argued that these measures clearly should not apply to savings and cooperative banks. This is broadly in line with a survey of the preferences of French and German MPs on reforms to the EMU by Blesse, Boyer, Heinemann, Janeba, and Raj (2019) where French MPs were found to be more strongly in favour of new Eurozone competencies.…”
Section: Framing and Polarizationsupporting
confidence: 88%
“…In line with H1, for the SSM and SRM/SRF, where German public opinion and economic interests were sceptical towards the EU's plans, but public salience was lower, the government parties took on board the interests of stakeholders and argued that these measures clearly should not apply to savings and cooperative banks. This is broadly in line with a survey of the preferences of French and German MPs on reforms to the EMU by Blesse, Boyer, Heinemann, Janeba, and Raj (2019) where French MPs were found to be more strongly in favour of new Eurozone competencies.…”
Section: Framing and Polarizationsupporting
confidence: 88%
“…While net fiscal benefits are an imperfect measure of the benefits from integration, many political debates surround such concepts and these concerns are thus likely to play out in the political arena. Previous research investigating these questions has already found strong support for the role of nationality in determining MP preferences, confirming that German politicians are less integrationist than their French counterparts (Blesse et al, 2019a).…”
Section: Theoretical Frameworkmentioning
confidence: 58%
“…This amounts to a response rate of 12.7%, which is common among parliamentary surveys (e.g., Blesse et al, 2019aBlesse et al, , 2019bDeschouwer et al, 2014). Table 1 summarizes (RN).…”
Section: Survey Design and Party Classificationsmentioning
confidence: 99%
“…Blesse et al (2020a) examine preferences of French and German politicians regarding European Monetary Union reforms. On governments' position taking in the 2010 European public debt crisis seeArmingeon and Cranmer (2018).…”
mentioning
confidence: 99%